Knowledge of breastfeeding in first-time mothers. Instituto Nacional Materno Perinatal, Lima 2019 - Alvarez Lopez, María del Mar (2021)
Materials and Methods: Quantitative, descriptive, transversal study. 276 postpartum first-time mothers of INMP were surveyed, with informed consent, using a validated questionnaire. Results: 80.4% of first-time mothers showed a regular level of knowledge while 8.3% showed a bad level of knowledge. The highest percentage of mothers with good level of knowledge were between 24 and 29 years old (38.71%); in contrast, mothers under or equal to 23 years old have the highest percentage of bad knowledge (47,82%). In addition, mothers from Province accounted the highest percentage of bad knowledge (73,91 %), more than double for those who are from Lima (26,1%). Also, we found that there is an association between the provenance and occupation of the mother with the level of knowledge. Conclusions: A regular level of knowledge on breastfeeding prevailed. As for the profile of mother with bad knowledge was under 23 years old, domestic partner, from Province, works and full secondary education; while the profile of mother with good knowledge was between 24 and 29, domestic partner, from Lima, housewife and unfinished college.